A Extensão do Poder Normativo das Agências Reguladoras no Direito Positivo Brasileiro - Tosta, Eduardo Andre Moreira (2004)
In Brazil, since the 1990 s already in the course of adapting to the new system, a vast program of destatization of public services took place. Several public service companies such as power supply and telephones were privatized. The oil sector was flexibilized, allowing private companies to participate in this important and strategic sector of the economic activity. The new model obliged the Brazilian State to make a structural adaptation, thus making a wide reform in the Public Administration in order for it to become more agile and have more decision capacity. In this scenario, a managerial Public Administration arises, focusing on efficiency. Regulatory Agencies are created with the clear objective of regulating the economy s several segments, mainly those related to the public services, which had been privatized. Although some of these services were turned into private enterprises, they still did not lose the State s tutorial supervision. On the other hand, it cannot be allowed that Public Administration totally controls these sectors, for then it would not have made sense to privatize them. However, public autarkic entities were created to regulate the private public services concessionaries activities. In synthesis, they were conceived to mediate the sectors natural conflicts with independence and exemption. In order to naturally develop their tasks, the Regulatory Agencies have great autonomy regarding the central power. In fact, it is a public law entity that has several prerogatives given by the legislator, not found in any other entity in our judicial system. Amongst these attributes, the normative capacity arises in importance, given through the law, through the legislative process.The present study has the objective of analyzing the legitimacy and the extension of this attribute given to these special autarkies. Copied from the Anglo-Saxon model, which adopts a legal standard with strong influence from the common law, the Agencies with normative powers are an innovation in our judicial system, whose roots are essentially related to the written law of Latin origin, extremely legalist. So, due to its importance in the Brazilian judicial system, the emission of sanction norms by a public entity different from the Legislative Power, requires a very detailed analysis of its possibility and if it s the case, of its extension and limits. This is the objective of this dissertation.